Prognostic factors of triple-negative inflammatory breast cancer based on SEER database - CHEN Shuyu, GAO Ya (Zhongguo linchuang yanjiu)
"Objective To investigate the clinicopathological features and survival prognostic factors of patients with triple-negative inflammatory breast cancer (TNIBC). Methods The data of patients with TNIBC from 2010 to 2015 were obtained from SEER database, and univariate analysis, multivariate analysis and Kaplan-Meier survival analysis were performed using the “survival” package in R statistical software. Results A total of 4 268 cases of inflammatory breast cancer were collected, including 1 023 cases of triple-negative subtype. Compared with non-TNIBC patients,TNIBC patients had a lower proportion of whites in ethnic distribution, a higher proportion of histological grade Ⅲ, a higher proportion of AJCC stage Ⅲ, and more patients without distant metastases, and more likely to receive chemotherapy (P＜0.05). Univariate Cox analysis showed that laterality, tumor diameter, AJCC stage, M stage, surgery and chemotherapy may be the influencing factors of overall survival (OS) (P＜0.05). Multivariate Cox analysis showed that laterality, tumor diameter and surgery were independent risk factors for OS in TNIBC patients, and the smaller the tumor (28-989 mm, HR=1.565, 95%CI: 1.061-2.309, P=0.024; ＞989 mm, HR=1.911, 95%CI: 1.205-3.030, P=0.006), locating in the right side (HR=0.719, 95%CI: 0.560-0.923, P=0.010), and the surgical treatment (HR=0.609, 95%CI: 0.423-0.876, P=0.008) were associated with better prognosis. Conclusion Laterality, tumor diameter, and surgery are independent influencing factors for survival prognosis in patients with TNIBC, and the smaller the tumor, locating in the right side, and surgery are associated with better prognosis."